Rapid Whole-Mount High-Resolution Imaging of Small Animal Vasculature for Quantitative Studies - Zhang, Daibo; Lindsey, Stephanie E (Journal of visualized experiments, 2025)
In small animal models of cardiovascular development and diseases, subject-specific computational simulations of blood flow enable quantitative assessments of hemodynamic metrics that are difficult to measure experimentally. Computational fluid dynamic simulations shed light on the critical roles of mechanics in cardiovascular function and disease progression. Acquiring high-quality volumetric images of the vessels of interest is central to the accuracy and reproducibility of morphological measurement and flow quantitation results. This study proposes a rapid, cost-effective, and accessible method for whole-mount high-resolution imaging of small animal vasculature using light-sheet fluorescence microscopy. The modified iDISCO+ (immunolabeling-enabled three-dimensional imaging of solvent-cleared organs) light-sheet sample preparation protocol involves (1) labeling vasculature with a fluorescent agent, (2) preserving the sample, and (3) rendering the sample transparent. Unlike classical iDISCO+, which uses immunohistochemical staining, the authors label vascular endothelium with FITC-tagged poly-L-lysine, an affordable non-specific fluorescent dye that is highly resistant to photo-bleaching, in a process termed "endo-painting." The rapid labeling reduces sample preparation time from approximately four weeks to less than 3 days. Furthermore, the use of minimally hazardous solvent ethyl cinnamate (ECi) as the clearing agent and imaging solution makes the samples safer to handle and compliant with a wider range of imaging facilities. The proposed protocol is applied to obtain highly resolved light-sheet fluorescence microscopy image stacks of the cardiovascular system in chick embryos ranging from day 3 (HH18) to day 8 (HH34). This study further demonstrates the suitability of this method for vascular quantitation through 3D reconstruction and computational hemodynamic modeling of a day 5 (HH 26) chick embryo.